2022
DOI: 10.1111/bcp.15532
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin utilization among older adults with different cognitive statuses enrolled in the National Alzheimer's Coordinating Center (2006–2019)

Abstract: This study aimed to examine gabapentin utilization trends among older adults with different cognitive statuses and investigate concurrent medication use of potentially inappropriate medications. Data were extracted from the National Alzheimer's Coordinating Center Uniform Data Set (2006–2019). We estimated the yearly prevalence of gabapentin use, both overall and within subgroups defined by cognitive status (normal, mild cognitive impairment and dementia) and demographics (age and sex) for participants aged 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In addition to the neurocognitive outcomes under study, we also found that the gabapentin initiators had higher prevalence of opioid use, as well as antidepressants, antipsychotics, benzodiazepines, and anxiolytics, sedatives, and hypnotics compared to nonusers. This result is consistent to our previous study that examined the concurrent use of gabapentin with CNSdepressant medications (Oh et al, 2022). As the FDA and the Beers 2019 criteria warn about using gabapentin concurrently with some medications due to risk of respiratory depression (U.S. Food and Drug Administration, 2019; By the 2019 American Geriatrics Society Beers Criteria ® Update Expert Panel, 2019), further studies are needed to examine the risk of concurrently using gabapentin with other CNS depressants in older adults.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the neurocognitive outcomes under study, we also found that the gabapentin initiators had higher prevalence of opioid use, as well as antidepressants, antipsychotics, benzodiazepines, and anxiolytics, sedatives, and hypnotics compared to nonusers. This result is consistent to our previous study that examined the concurrent use of gabapentin with CNSdepressant medications (Oh et al, 2022). As the FDA and the Beers 2019 criteria warn about using gabapentin concurrently with some medications due to risk of respiratory depression (U.S. Food and Drug Administration, 2019; By the 2019 American Geriatrics Society Beers Criteria ® Update Expert Panel, 2019), further studies are needed to examine the risk of concurrently using gabapentin with other CNS depressants in older adults.…”
Section: Discussionsupporting
confidence: 93%
“…benzodiazepines) and opioid analgesics significantly increases adverse events, such as respiratory depression and mortality 6,21 . Moreover, gabapentinoid use has also been associated with increased risks of suicidal ideation and behaviour, particularly among adolescents and young adults (15–24 years) and women 22–24 . Furthermore, physical dependence, tolerance and withdrawal from gabapentinoids have been well documented at both recommended dosages and supratherapeutic dosages 6,22,25,26 …”
Section: Introductionmentioning
confidence: 99%
“…6,21 Moreover, gabapentinoid use has also been associated with increased risks of suicidal ideation and behaviour, particularly among adolescents and young adults (15-24 years) and women. [22][23][24] Furthermore, physical dependence, tolerance and withdrawal from gabapentinoids have been well documented at both recommended dosages and supratherapeutic dosages. 6,22,25,26 In cases where a drug is no longer needed or is associated with more harm than benefits, the medicine should cease (or reduce in dose).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14-16) Furthermore, physical dependence, tolerance and withdrawal from gabapentinoids have been well documented at both recommended dosages and supratherapeutic dosages. (2,14,17,18) In cases where a drug is no longer needed or is associated with more harms than benefits, the medicine should cease (or reduce in dose). Deprescribing is the complex process of tapering or ceasing unnecessary medication, aimed at improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%